Global security in the twenty-first century the quest for power and the search for peace - Kay, Sean (Rowman & Littlefield Publishers, 2015)
This thoroughly updated edition offers a balanced introduction to contemporary security dilemmas throughout the world. Writing in an engaging style, Sean Kay integrates traditional and emerging challenges in one easily accessible study that gives readers the tools they need to develop a thoughtful and nuanced understanding of global security.